2018
DOI: 10.1021/acs.estlett.8b00395
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation and Mineralization of Perfluorooctanoic Acid by a New Petitjeanite Bi3O(OH)(PO4)2 Microparticle Ultraviolet Photocatalyst

Abstract: Water treatment techniques for destructive removal of perfluoroalkyl substances (PFAS) have only recently begun to emerge in the research literature, comprising unconventional advanced oxidation and reduction methods. Photocatalytic degradation of PFAS has not been widely pursued, which is a result of the limited ability of common semiconductor materials to induce C−F bond cleavage in aqueous systems. Herein, degradation of perfluorooctanoic acid (PFOA) by bismuth phosphate photocatalysts under ultraviolet irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 34 publications
5
80
0
Order By: Relevance
“…For the effective potential difference of CB between BiOCl and β-FeOOH, the e − of β-FeOOH can transfer to the CB of BiOCl through the fabricated heterojunction interfaces. In this process, the transferred e − can be captured by H 2…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the effective potential difference of CB between BiOCl and β-FeOOH, the e − of β-FeOOH can transfer to the CB of BiOCl through the fabricated heterojunction interfaces. In this process, the transferred e − can be captured by H 2…”
Section: Resultsmentioning
confidence: 99%
“…However, while developing the industry, it also caused a lot of energy consumption. In order to be sustainable, energy crisis have attracted more and more attention . Therefore, how to solve the above problem efficiently becomes a hot topic of research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After three hours of UV treatment, 98.8% of PFOA was degraded and the defluorination rate was 31.6% under anaerobic conditions. Sahu et al used a bismuth phosphate photocatalyst (Bi 3 O(OH)(PO 4 ) 2 ) for the UV treatment of PFOA [ 95 ]. This material showed quantitative PFOA degradation after one hour and a defluorination rate of approximately 60% after two hours, which was much higher than for other catalysts (Ga 2 O 3 , BiPO 4 and TiO 2 ) in this experiment.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
“…[7] Cates et al reported a Bi 3 O(OH) (PO 4 ) 2 microparticle ultraviolet photocatalyst for PFOA degradation. [8] A recent study found that PFOA molecules can bind well to the surface of commercial In 2 O 3 through their terminal carboxylate groups via a bidentate or bridging configuration. [9] Thus, upon UV irradiation, In 2 O 3 shows a significant photocatalytic degradation ability towards PFOA.…”
Section: Introductionmentioning
confidence: 99%